Multiple metabolic requirements for size homeostasis and initiation of division in Saccharomyces cerevisiae - Shivatheja Soma; Kailu Yang; Maria I. Morales; Michael Polymenis (Microbial Cell)
Most cells must grow before they can divide, but it is not known how cells determine when they have grown enough so they can commit to a new round of cell division. Several parameters affect the timing of initiation of division: cell size at birth, the size cells have to reach when they commit to division, and how fast they reach that size. We report that Saccharomyces cerevisiae mutants in metabolic and biosynthetic pathways differ in these variables, controlling the timing of initiation of cell division in various ways. Some mutants affect the size at birth, size at initiation of division, the rate of increase in size, or any combination of the above. Furthermore, we show that adenylate kinase, encoded by ADK1, is a significant determinant of the efficiency of size control mechanisms. Finally, our data argue strongly that the cell size at division is not necessarily a function of the rate cells increase in size in the G1 phase of the cell cycle. Taken together, these findings reveal an unexpected diversity in the G1 cell cycle phenotypes of metabolic and biosynthetic mutants, suggesting that growth requirements for cell division are multiple, distinct and imposed throughout the G1 phase of the cell cycle.